Ambiguity and the historical equity premium - Mukerji, S; Sheppard, K; Collard, F; Tallon, J (University of Oxford, 2011)
This paper assesses the quantitative impact of ambiguity on the historically observed financial asset returns and prices. The single agent, in a dynamic exchange economy, treats the conditional uncertainty about the consumption and dividends next period as ambiguous. We calibrate the agent's ambiguity aversion to match only the first moment of the risk-free rate in data and condition the uncertainty each period on the actual, observed history of (U.S.) macroeconomic growth outcomes. Ambiguity aversion accentuates the conditional uncertainty endogenously in a dynamic way, depending on the history; e.g., it increases during recessions. We show the model implied time series of asset returns match observed return dynamics of first and second conditional moments, very substantially. In particular, we find the time-series properties of our model generated equity premium, which may be regarded as an index measure of revealed uncertainty, relates very closely to those of the macroeconomic uncertainty index recently developed in Jurado, Ludvigson and Ng (2013). New version: January 2015